RANCANG BANGUN COVER LAMPU CABIN KENDARAAN TOYOTA AVANZA MENGGUNAKAN KOMPOSIT SERAT PANDANUS TECTORIUS DENGAN MATRIKS EPOXY - mochamad (Pengelolaan Penerbitan Publikasi Ilmiah (P3I) Politeknik Negeri Madiun, 2024)
The use of plastic must be reduced immediately because it causes environmental problems and losses. Plastic contains dangerous particles, as it is known that when burned it can produce toxic gases. Plastic is a light material, so its use in vehicles can reduce vehicle weight. This weight reduction can improve fuel efficiency. Even though there are advantages to using plastic, it is important to remember that using plastic also causes environmental pollution problems. A substitute for plastic that is easily decomposed is biocomposite. The biocomposite here is a combination of Pandanus Tectorius fiber with an epoxy matrix. Then make a cabin light cover. This research provides positive results regarding the use of natural fiber composites in the automotive industry. Pandanus Tectorius fiber composite cabin light covers with an epoxy matrix have the potential to replace conventional cabin light covers because the raw material is made from natural fiber, which is likely to reduce environmental pollution problems and has good strength and heat conductivity.